2010
DOI: 10.1021/je900859n
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagrams for the Ternary Na2O−Al2O3−H2O System at (150 and 180) °C

Abstract: The full alkali concentration range phase diagrams of the Na2O−Al2O3−H2O system were constructed at (150 and 180) °C. The compositions of the clear liquids and wet solid phases were analyzed by inductively coupled plasma atomic emission spectrometry (ICP-AES), and the results show that, as the Na2O concentration increases, the Al2O3 solubility initially increases monotonically, to maximum values of 100 w (mass fraction) = 33.58 and 35.86 at (150 and 180) °C, respectively, and then decreases. At both temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…13 According to the research, it was found that the equilibrium solid phases of this ternary system diversified with temperature and concentration. At low concentrations, the equilibrium solid was determined to be Al 2 O 3 •3H 2 O at 368.15 and 383.15 K, 14 prior to becoming Al 2 O 3 •H 2 O at 403.15, 15 423.15, and 453.15 K. 16 Meanwhile, with an increase in the Na In general, it needs a broad temperature operating range (from 323.15 to 353.15 K) for separating the soluble alumina from the alkaline leaching solution, since the flowsheet could include cooling crystallization. Nevertheless, the existing phase equilibrium data of the corresponding system at this temperature range are deficient.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 According to the research, it was found that the equilibrium solid phases of this ternary system diversified with temperature and concentration. At low concentrations, the equilibrium solid was determined to be Al 2 O 3 •3H 2 O at 368.15 and 383.15 K, 14 prior to becoming Al 2 O 3 •H 2 O at 403.15, 15 423.15, and 453.15 K. 16 Meanwhile, with an increase in the Na In general, it needs a broad temperature operating range (from 323.15 to 353.15 K) for separating the soluble alumina from the alkaline leaching solution, since the flowsheet could include cooling crystallization. Nevertheless, the existing phase equilibrium data of the corresponding system at this temperature range are deficient.…”
Section: Introductionmentioning
confidence: 98%
“…According to the research, it was found that the equilibrium solid phases of this ternary system diversified with temperature and concentration. At low concentrations, the equilibrium solid was determined to be Al 2 O 3 ·3H 2 O at 368.15 and 383.15 K, prior to becoming Al 2 O 3 ·H 2 O at 403.15, 423.15, and 453.15 K . Meanwhile, with an increase in the Na 2 O concentration at 383.15 K, the equilibrium solid transforms from Na 2 O·Al 2 O 3 ·2.5H 2 O to a mixture of 4Na 2 O·Al 2 O 3 ·12H 2 O and 6Na 2 O·Al 2 O 3 ·12H 2 O …”
Section: Introductionmentioning
confidence: 99%
“…Gessner once studied the stable liquid–solid phase equilibria for the ternary system Na 2 O–Al 2 O 3 –H 2 O at low temperature. Zhang et al investigated the phase equilibrium for the same system at high temperature by the Schreinemaker method. Du measured the phase equilibria for the ternary system K 2 O–Al 2 O 3 –H 2 O at 313.15 K by the isothermal method and proposed a separation method of aluminum salt from the alkali solution according to the phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…The phase equilibrium of the ternary system of Na 2 O−Al 2 O 3 −H 2 O was also studied in the literature at high alkaline conditions. 10,11 In this study, Na 2 CrO 4 solubility in the ternary system of NaOH−H 2 O−Na 2 CrO 4 was first measured under different temperatures and NaOH concentrations. Subsequently, the solubility of Na 2 CrO 4 , NaAlO 2 , and Na 2 SiO 3 in the quaternary systems of NaOH−H 2 O−Na 2 CrO 4 −NaAlO 2 and NaOH− H 2 O−Na 2 CrO 4 −Na 2 SiO 3 , and the quinary system of NaOH−H 2 O−Na 2 CrO 4 −NaAlO 2 −Na 2 SiO 3 was studied at temperatures from 353.15 to 403.15 K and specific NaOH concentrations at 400, 500, and 600 g·L −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%